2022
DOI: 10.11648/j.cmr.20221102.11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Somatotype in Taekwondo: Systematic Review

Abstract: The Taekwondo, as in other sports, athletes who have certain physical characteristics have an advantage over their opponents, in this sense, success in the practice of taekwondo requires certain types of physical, physiological, psychological and social capacities, so those athletes whose characteristics anthropometric are favorable to them, they may be benefited over others. This is why we set ourselves the objective of reviewing the information regarding the somatotype presented by athletes who practice taek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Consequently, a multitude of recent studies focusing on the somatotyping of female athletes have been conducted and published by various researchers (Luthra et al 2021 This discernible pattern of gender disparity in sports research is consistent with findings from a systematic review on gender inequalities in sports medicine research by Paul et al (2023), who reported a similar imbalance between male and female subjects. Additional review articles on sports research by Shahidi et al (2023) in ball sports and Pena-Sanchez et al (2022) in taekwondo have also highlighted comparable patterns of gender disparity. Therefore, it is evident that this issue is not confined solely to India but is a global phenomenon.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, a multitude of recent studies focusing on the somatotyping of female athletes have been conducted and published by various researchers (Luthra et al 2021 This discernible pattern of gender disparity in sports research is consistent with findings from a systematic review on gender inequalities in sports medicine research by Paul et al (2023), who reported a similar imbalance between male and female subjects. Additional review articles on sports research by Shahidi et al (2023) in ball sports and Pena-Sanchez et al (2022) in taekwondo have also highlighted comparable patterns of gender disparity. Therefore, it is evident that this issue is not confined solely to India but is a global phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, various researchers have undertaken short reviews, systematic reviews, and meta-analyses on the somatotypes of athletes in diverse fields. For instance, Rakovick et al (2015) gave a systematic analysis of elite athletes' somatotype, Sterkowicz-Przybycien et al (2012) focussed on judokas, Sterkowicz-Przybycien and Gualdi-Russo (2019) reported a metanalysis on gymnasts, while Pena-Sanchez et al (2022) conducted a systematic review explicitly addressing on somatotypes of taekwondo players.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the scientific literature reveals a diverse approach to the potential impact of somatotypes on success in sport, it is also known that predisposition is only one of the components which, together with other factors such as the training process, nutritional status, psychological preparation, plays a key role in a successful career of athletes meaning 'an athlete is born and created' [20]. Although it is obvious that an anthropometric profile may refer to the athletes' suitability to engage in high-performance sport [26][27][28][29][30][31][32][33], there is an existing research gap in explaining the relationship between the body composition profile, nutritional status and the quantified expression of the morphological conformation in elite athletes. Therefore, the transition between somatotypes and their practical implications in sports should be explored at a more advanced level.…”
Section: Introductionmentioning
confidence: 99%